The relationships between sprint run and strength parameters in young athletes and non-athletes - Cunha, L.; Ribeiro, J.; Fernandes, O.; Valamatos, M. J.; Pinto, R.; Santos, P. (ISBS - Conference Proceedings Archive (Konstanz), 2007)
The aim of this study was to examine the relationships between the sprint run and strength tests, which measure the capability to produce force in isometric, pure concentric and stretch shortening cycle muscular actions. The seventy two subjects were assessed for six tests 60m sprint run, to evaluate the speed, and isometric leg-press, squat jump, countermovement jump, drop jump, and 5 horizontal jumps, to evaluate strength parameters. The 5 jumps, was the most important predictor of the 60m sprint time, maybe because of is cyclic and horizontal characteristics (more similar to the specific movement of sprint run). We suppose that the reason for results do not explain different relationship between tests and sprint performance, in young athletes can be find in multifactorial characteristics of sprinting performance and the characteristics of the subjects, youngest have reduced training adaptation.